Transforming psychology education to include global mental health. (15th March 2023) - Khoury, Brigitte; De Castro Pecanha, Viviane
Abstract: In recent years, the reality of global migration has brought the lack of understanding of mental health needs across different cultures into sharp focus. Psychology programs are not up to date on global issues and are often experienced as inadequate in preparing graduates to meet the challenges of society today. The field of education and training in psychology has hardly evolved since the last two decades. On the other hand, the mental health needs arising locally and globally require a knowledge base and a set of skills future psychologists need to have in order to be able to work and grow professionally. In addition, most psychologists in the western world are bound, at some point in their career, to be in contact with immigrants or refugees to offer them services and be a source of support for such a vulnerable population. Also, the field of psychology is witnessing more movement among psychologists than ever before, whereby many professionals move to another country, to work, volunteer, gain or provide training, consult and much more. This requires a certain level of preparation, which psychologists need to be aware of and ready to engage in before and after they move. This article highlights different psychology programs around the world that include global mental health in their programs. It discusses essential aspects and skills that psychologists need to learn to be prepared to work globally with various populations and to expand their skills beyond service providing to more management and policy work. Topics such as human rights and social justice, advocacy, health management and policymaking are addressed as important competencies to be gained during the education and training of future psychologists.